Violence and new religious movements - Lewis, James R. (Oxford University Press, 2011)
The connection between cults and violence has been a topic of intense public interest that has been fueled by dramatic incidents of mass violence involving certain new religious movements (NRMs). The present volume represents the culmination of decades of reflection by scholarly specialists